APPLICATION OF COBIT 2019 IN INFORMATION SECURITY: the importance of prevention - de Melo Franco, Isabela (Revista Interface Tecnológica, 2023)
The number of cyberattacks has been growing exponentially in recent years, demanding greater precaution from organizations regarding information security. In this scenario, the objective of this article is to present, through a bibliographical research, the Control Objectives for Information and Related Technologies 2019, better known as COBIT 2019, as a support structure for companies to organize themselves from the perspective of cybersecurity, through governance and management. In addition, other concepts such as types and real cases of cyberattacks, as well as expected investments in information security are developed. Finally, it is expected that with this research it will be possible to reach a higher level of awareness regarding the protection of information systems, prevention and investments against cyberattacks; encourage the adoption of the COBIT 2019 framework and its key processes APO13 and DSS05 (related to security) in companies and encourage the preparation of studies in the area.